2011
DOI: 10.1016/j.urology.2011.03.071
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific Antigen/Solvent Interaction Analysis: A Preliminary Evaluation of a New Assay Concept for Detecting Prostate Cancer Using Urinary Samples

Abstract: Objectives To provide preliminary clinical performance evaluation of a novel CaP assay, PSA/SIA (Solvent Interaction Analysis) that focused on changes to the structure of PSA. Methods 222 men undergoing prostate biopsy for accepted clinical criteria at three sites (University Hospitals Case Medical Center in Cleveland, Cleveland Clinic, and Veterans Administration Boston Healthcare System) were enrolled in IRB approved study. Prior to TRUS guided biopsy, patients received DRE with systematic prostate massage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
(18 reference statements)
0
7
1
Order By: Relevance
“…Based on these results, adequate IL-based ABS can be used to effectively pre-treat human urine samples, leading to the concentration and quantification of more than one form of PSA while paving the way to PCa differential cancer diagnosis and monitoring. The approach here proposed www.nature.com/scientificreports/ is different from that reported in previous studies dealing with ABS composed of two polymers [14][15][16] . Instead of analysing the partition behaviour of PSA and respective isoforms, and where the partition coefficient is directly used in diagnosis, in this work IL-based ABS are used as pre-treatment strategies of biological samples, allowing the quantification of cancer biomarkers by SE-HPLC and not by immunoassays as usually carried out [14][15][16] .…”
Section: Extraction and Concentration Of Prostate Specific Antigen (Pcontrasting
confidence: 61%
See 2 more Smart Citations
“…Based on these results, adequate IL-based ABS can be used to effectively pre-treat human urine samples, leading to the concentration and quantification of more than one form of PSA while paving the way to PCa differential cancer diagnosis and monitoring. The approach here proposed www.nature.com/scientificreports/ is different from that reported in previous studies dealing with ABS composed of two polymers [14][15][16] . Instead of analysing the partition behaviour of PSA and respective isoforms, and where the partition coefficient is directly used in diagnosis, in this work IL-based ABS are used as pre-treatment strategies of biological samples, allowing the quantification of cancer biomarkers by SE-HPLC and not by immunoassays as usually carried out [14][15][16] .…”
Section: Extraction and Concentration Of Prostate Specific Antigen (Pcontrasting
confidence: 61%
“…Previous works reported on the use of ABS composed of two polymers, namely dextran and ficoll, to extract PSA 14 ; nevertheless, these systems do not allow the complete extraction and concentration of PSA in one phase. Accordingly, subsequent studies 15,16 focused on the quantification of PSA isoforms and determination of their partition coefficients between the ABS coexisting phases. Overall, in all studies reported so far, it was not possible to completely extract PSA to a given phase, thus preventing the use of ABS in pre-treatment strategies of human fluids as proposed in the current work.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore they can be used for the discriminating distribution of added solutes. ATPSs have been used for separation of biological macromolecules and particles for over 50 years [5][6][7] and recently found use in a variety of analytical applications as well [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The constant decrease in specific mortality from prostate cancer observed in recent years in the USA and France through data from cancer registers, partly responds to the interest in individual screening for men aged 50 to 75 with a long life expectancy greater than 10 years [3] [4]. The diagnosis of prostate cancer is established by prostate biopsy and allows a real mapping of the prostate to be carried out [5] [6]. Many prostate cancers are detected based on high plasma levels of prostate specific antigen (PSA > 4 ng/mL), a glycoprotein normally expressed by prostate tissue [6].…”
Section: Introductionmentioning
confidence: 99%